2005
DOI: 10.1152/ajplung.00007.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-6 in murine airway responses to ozone

Abstract: This study sought to examine the role of interleukin-6 (IL-6) in ozone (O3)-induced airway injury, inflammation, and hyperresponsiveness (AHR). Subacute (72 h) exposure to 0.3 ppm O3significantly elevated bronchoalveolar lavage fluid (BALF) protein, neutrophils, and soluble TNF receptors (sTNFR1 and sTNFR2) in wild-type C57BL/6 (IL-6+/+) mice; however, all four outcome indicators were significantly reduced in IL-6-deficient (IL-6−/−) compared with IL-6+/+mice. Acute O3exposure (2 ppm for 3 h) increased BALF pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
86
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 45 publications
19
86
1
1
Order By: Relevance
“…It is plausible that systemic inflammation does affect the airways. Indeed genetically IL-6-deficient, ozoneexposed mice have reduced airway neutrophils [29], while elevated CRP is associated with accelerated lung function decline independent of BMI [30]. In this study, asthma independently increased plasma levels of IL-6 by ,50%.…”
mentioning
confidence: 45%
“…It is plausible that systemic inflammation does affect the airways. Indeed genetically IL-6-deficient, ozoneexposed mice have reduced airway neutrophils [29], while elevated CRP is associated with accelerated lung function decline independent of BMI [30]. In this study, asthma independently increased plasma levels of IL-6 by ,50%.…”
mentioning
confidence: 45%
“…The increased levels of IL-6 in BALF following ozone exposure were accompanied by simultaneous increases in IL-6 mRNA in lung tissue (24;25), indicating that changes in BALF concentration of IL-6 were also reflected in the lung expression of IL-6. However, although BALF neutrophils were reduced following 3ppm exposure to ozone for 2 hours in IL-6 knockout mice compared to IL-6 transgenic mice, AHR was not affected (26), indicating a dissociation of IL-6 expression and AHR. Similar dissociation between AHR and TNFα expression has been reported.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have shown that bradykinin-induced increase in IL-6 protein and mRNA is inhibited by IL-13 in human ASM cells and that IL-6 expression was also found to be bradykinin B 2 receptor-dependent [43]. Interestingly, IL-6 has been shown to play a pro-inflammatory role in ozone-induced inflammation [44].…”
Section: Il-13 and Ozone As Williams Et Almentioning
confidence: 97%